Peningkatan Pemahaman Akibat Hukum Terhadap Perkawinan Anak Di Desa Bantur Kabupaten Malang - Fahmi Arif Zakaria; Darajatun Indra Kusuma Wijaya; Anindya Bidasari; Ririen Indria Dian Ambarsari; Christian Ade Wijaya (jurnal ABDIMAS Indonesia, 2024)
Marriage is a sacred contract between a man and a woman as husband and wife, which aims to build a Sakina family. Marrying into a Sakina family requires not only physical and psychological preparation, but also social, financial, emotional and responsible preparation. Therefore, limiting the age of marriage is an important principle. This is because the Marriage Law and Civil Code clearly regulate and define the age limit for marriage in such a way that all prospective husband and wife must be truly mature physically and mentally. However, underage marriage still occurs in Bantul Village, which has an impact on family welfare. Based on the explanation above, the author formulates the problem as follows: (1) What are the factors causing underage marriage in Bantul, Malang Regency?; (2) What is the impact of underage marriage on household welfare? By using a qualitative descriptive approach to describe some of the data obtained from the field through interviews, observation, or documentation as data collection methods. Furthermore, it proceeds to the process of data reduction, data presentation, and conclusion drawing by using data analysis techniques. In addition, the analysis process is also supported by literature review as a reference to refine the data obtained from practice. Such a process allows us to draw conclusions as answers to the two questions above. From the research findings, it can be concluded that the factors causing underage marriage in Bantul village are economic factors, education, parents, customs, and pregnancy outside marriage.